Schistosoma mansoni secretes a chemokine binding protein with anti-inflammatory activity. - FALLON, PADRAIC (Rockefeller University Press, 2005)
The coevolution of humans and infectious agents has exerted selective pressure on the immune system to control potentially lethal infections. Correspondingly, pathogens have evolved with various strategies to modulate and circumvent the host's innate and adaptive immune response. Schistosoma species are helminth parasites with genes that have been selected to modulate the host to tolerate chronic worm infections, often for decades, without overt morbidity. The modulation of immunity by schistosomes has been shown to prevent a range of immune-mediated diseases, including allergies and autoimmunity. Individual immune-modulating schistosome molecules have, therefore, therapeutic potential as selective manipulators of the immune system to prevent unrelated diseases. Here we show that S. mansoni eggs secrete a protein into host tissues that binds certain chemokines and inhibits their interaction with host chemokine receptors and their biological activity. The purified recombinant S. mansoni chemokine binding protein (smCKBP) suppressed inflammation in several disease models. smCKBP is unrelated to host proteins and is the first described chemokine binding protein encoded by a pathogenic human parasite and may have potential as an antiinflammatory agent.
PUBLISHED
Keywords: Clinical Medicine